Pengaruh pemberian ekstrak etanol daun sirsak (Annona muricata l.) Terhadap gambaran histopatologi hepar dan pembuluh darah aorta kelinci (Oryctolagus cuniculus) hiperkolesterolemia - Maria A.W. Dede; Putri Pandarangga; Meity M. Laut (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2019)
Hypercholesterolemia is a disease of cholesterol metabolism disorders caused by elevated levels of cholesterol in the blood. This condition can lead to fatty change, hidropis degeneration, cell injury and inflammatory cells infiltration in the liver and fatty infiltration and inflammatory cells in the tunica area of aorta. The purpose of this study was to determine the effect of ethanol extract of leaves of the soursop (Annona muricata L.) for the treatment of hypercholesterolemia in rabbits (Oryctolagus cuniculus) to see whether there is a pile of fatty plaques in the aortic and the deposition of fat in hepatocytes through histopathologic image,which supported by examination of the cholesterol content in the blood. This research uses experimental animals as much as 12 local rabbits, male sex, weight ± 500 to 1000 grams and aged up to 2 months ± 1.5 months. Animals are grouped into four groups of three in each group, the group (A) is a negative control group in which only gived the standard food, group (B) is a positive control group by feeding a high-fat is lard as much as 2,6 mL/500grBB to 5.2 mL/ 1000grBB, groups of (C) is a group therapy by soursop leaves of ethanol extract at a dose of 8 mg/500grBB up to 17 mg/1000grBB, and groups (D) is a group treated with simvastatin at a dose of as much as 0.7 mg/500grBB to 1.4 mg/1000grBB. The results show that that there is no difference between the effect of soursop leaves ethanol extract and simvastatin in lowering blood cholesterol levels coursing through changes in lesions of the liver and aorta. It can be concluded that the therapy of soursop leaves of ethanol extract and simvastatin can protect the liver tissue structures and aorta blood vessels in hypercholesterolemia rabbit.